Writing a case report - Peh, W.C.G.; Ng, K.H. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2010)
A case report is a description of a single case with unique features. This includes a previously-unreported clinical condition, previously-unreported observation of a recognised disease, unique use of imaging or diagnostic test to reveal a disease, previously-unreported treatment in a recognised disease, or previously-unreported complication of a procedure. Case reports should be short and focused, with a limited number of figures and references. The structure of a case report usually comprises a short unstructured (or no) abstract, brief (or no) introduction, succinct but comprehensive report of the case, and to-the-point discussion.